Secretory autophagy holds the key to lysozyme secretion during bacterial infection of the intestine - Delorme-Axford, Elizabeth (Autophagy, 2018)
In 2013, Dr. Lora Hooper and colleagues described the induction of antibacterial macroautophagy/autophagy in intestinal epithelial cells as a cytoprotective host defense mechanism against invading Salmonella enterica serovar Typhimurium (S. Typhimurium). Canonical autophagy functions in a primarily degradative capacity to safeguard cells and ensure survival during stress conditions, including pathogen infection. In contrast, secretory autophagy has emerged as an alternative nondegradative mechanism for cellular trafficking and unconventional protein secretion. More recently, a study by Bel et al. from Dr. Hooper's lab describes how intestinal Paneth cells exploit the endoplasmic reticulum (ER) stress response to release antibacterial lysozyme through secretory autophagy in response to S. Typhimurium infection.